THE ‘AXIS’ OF POLITICAL POWER IN NIGERIA; ‘CAN NIGERIA BE UNIQUE AGAIN’? ‘AN ENDURING UNITY’ - Danladi, Shaibu Sunday (European Scientific Journal, ESJ, 2013)
This study dealt with the political commentary of Nigeria, and it investigates the issues challenging the contemporary government destination as the federation of Nigeria. It explores the questions of political power structure throughout the country drawing from the 1999 transition to democratic positioning. The fundamental analyses from this study make an attempt to explain the political psychological forecast challenging the bureaucratic affairs domestically, and it further traces the most concrete neglected evidence shaping the direction of progress through the country as well the dimension under which the current institutional conflicts were being established. Instability advances, Tension widespread in Nigeria. It raises the questions designing disunity within the country in both past and the present political power play in Nigeria. The study illustrates on ‘How the same puzzles of the past may have signaled another wave of distraction on the way of the country. The interest of this poli-psychological explanation helps us to undercover various political calculations shaping and re-designing of the present-day democratic institution in Nigeria. The studies explore the questions of the declining status of the current Nigeria nation and further beg us to understand the dichotomy under which the vision of the continuing integration in Nigeria could be explained. The framework of this study is handing out with an influential evidence why Nigeria may survive beyond nor even disappeared in some technical misfortunes ‘if’ there are not urgently addressed. While it suggests that the situation could be well-contained if, to some extent, a key visionary lens is being modern by the Nigeria leaders to re-define ‘Why Nigeria as sovereign nation’ ‘should remain as one’. The basic context hither is to diagnose the country as Nigeria is so far under a fragile illustration as ‘states’ for the few instead of a well organized as one integrated whole.